A critical engagement Sustainable Development Goals and the problem of ‘race’: Living Rights Festival - Soudien, Crain (New Agenda: SA Journal of Social and Economic Policy, 2025)
How do we conceptualise and develop a global development agenda that is attentive to the needs, requirements and entitlements of all the world’s people? In this contribution I problematise dominant approaches to development and the ways in which these approaches, firstly, conceptualise ideas about the ‘universal’ and, secondly, erase, silence and marginalise particular groups of people. With this backdrop, I focus on the UN’s Sustainable Development Goals (SDGs) and particularly their conceptualisation. Of particular interest is how the design of the SDGs deal with the fundamental objective underpinning this global intervention – that of inclusion. The argument I will make is that dominant development discourses, including the SDG project, have struggled to deal with the realities and effects of exclusion and marginalisation as they take expression and are manifested in processes of racialisation, gender discrimination and class formation.